2000
DOI: 10.1002/1531-8249(200008)48:2<254::aid-ana17>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Ramsay Hunt syndrome in children

Abstract: In a retrospective study, 52 children were diagnosed with Ramsay Hunt syndrome. The facial palsy was milder and complete recovery of the function was achieved in 78.6% of patients. Associated cranial neuropathies were less common in children than in adults. The timing of vesicle appearance tended to be delayed in children. In preschool children, Ramsay Hunt syndrome was rare, although the frequency has recently increased. The syndrome is relatively common in older children. This study suggested that vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 0 publications
0
44
0
8
Order By: Relevance
“…The counterpart among patients with Ramsay Hunt syndrome is characterised by peripheral facial paralysis without ear or mouth rash, and the presence of either a fourfold rise in antibody to VZV or the detection of VZV DNA in skin, blood mononuclear cells, or middle ear fluid. In the retrospective study by Hato et al ,19 of 1705 patients with ipsilateral facial palsy without vesicles, the data imply that 42 (2.4%) had zoster sine herpete. In a study of 32 patients with isolated peripheral facial palsy, Murakami et al 25identified zoster sine herpete in six (19%) of the patients based on a fourfold rise in serum antibody titre to VZV.…”
Section: Ramsay Hunt Syndrome Zoster Sine Herpetementioning
confidence: 96%
See 2 more Smart Citations
“…The counterpart among patients with Ramsay Hunt syndrome is characterised by peripheral facial paralysis without ear or mouth rash, and the presence of either a fourfold rise in antibody to VZV or the detection of VZV DNA in skin, blood mononuclear cells, or middle ear fluid. In the retrospective study by Hato et al ,19 of 1705 patients with ipsilateral facial palsy without vesicles, the data imply that 42 (2.4%) had zoster sine herpete. In a study of 32 patients with isolated peripheral facial palsy, Murakami et al 25identified zoster sine herpete in six (19%) of the patients based on a fourfold rise in serum antibody titre to VZV.…”
Section: Ramsay Hunt Syndrome Zoster Sine Herpetementioning
confidence: 96%
“…A retrospective review of 2076 patients presenting with unilateral facial palsy, with or without vesicles, from 1976 to 1996 in Japan19 disclosed a similar incidence of Ramsay Hunt syndrome in adults and children over age 6 years. In that study, the syndrome was defined as unilateral facial palsy, herpetic vesicles on the ear or oral mucosa, and vestibulocochlear dysfunction.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…VZV causes the RHS. Some patients develop peripheral facial paralysis without ear or mouth rash associated with either a fourfold rise in antibody to VZV or the presence of VZV DNA in auricular skin, blood MNCs, middle ear fluid, or saliva (Hato et al 2000). In a study of 32 patients with isolated peripheral facial palsy, Murakami et al (1998) identified RHS zoster sine herpete in six (19%) of the patients based on a fourfold rise in serum antibody titer to VZV; four of these six patients were positive for VZV DNA by PCR when geniculate zone skin scrapings were studied.…”
Section: Ramsay Hunt Syndromementioning
confidence: 99%
“…The rash can also affect the face and the omolateral two-thirds anterior part of the tongue and palate 2 3. Remarkably, not all the symptoms may be present; in the early phase of the disease, especially in children, vesicular rash may be absent (ie, zoster sine herpete), and pain and hyperaemia cutis along the affected nerve are typical clinical features 4. VZV reactivation should also be considered without facial palsy as affecting only the sensory portion of cranial nerve VII5; besides, VZV is responsible for one-third of isolated palsy and can be misdiagnosed as idiopathic Bell’s palsy 6.…”
Section: Answer To Questionmentioning
confidence: 99%